2020
DOI: 10.1002/hed.26585
|View full text |Cite
|
Sign up to set email alerts
|

Selective embolization of lingual artery in transoral robotic surgery for the management of recurrent base of tongue carcinomas

Abstract: Background: The incidence of oropharyngeal carcinoma has been on the rise in recent decades. About 30% of patients who undergo definitive chemoradiation as the initial treatment present with residual/recurrent disease. In such a situation, surgical salvage either in the form of traditional open surgery or transoral robotic surgery (TORS) remains a viable treatment option. However, the extensive vascular supply of the posterior tongue and tonsillar bed increases the risk of perioperative bleeding, which is a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This shows that prophylactic arterial ligation of the LA may be beneficial for patients that are at an increased risk for severe bleeding events, such as those getting radiation treatment prior to the TORS procedure 2 . A study about selective embolization of the LA in TORS as management of perioperative bleeding was presented by Rao et al 13 The prospective study consisted of five patients with recurrent or residual midline BOT tumors who underwent TORS after selective LA embolization. None of the patients had any major perioperative bleeding or postprocedural complications, and the authors of the said study concluded that selective embolization of the feeder vessels provided a favorable bloodless surgical field without impacting the vascular integrity of the remnant tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that prophylactic arterial ligation of the LA may be beneficial for patients that are at an increased risk for severe bleeding events, such as those getting radiation treatment prior to the TORS procedure 2 . A study about selective embolization of the LA in TORS as management of perioperative bleeding was presented by Rao et al 13 The prospective study consisted of five patients with recurrent or residual midline BOT tumors who underwent TORS after selective LA embolization. None of the patients had any major perioperative bleeding or postprocedural complications, and the authors of the said study concluded that selective embolization of the feeder vessels provided a favorable bloodless surgical field without impacting the vascular integrity of the remnant tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have discussed selective embolization of the LA and transcervical ligation as possible techniques for reducing the risk of both peri-and postoperative hemorrhage during TORS procedures. 2,13 Kubik et al 2 presented a retrospective study that identified risk factors of hemorrhage after TORS for oropharyngeal squamous cell carcinoma. In the study, it was reported that 13.2% of the patients experienced postoperative hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Complications following TORS surgery have been well-described, including hemorrhage, airway compromise, chronic dysphagia, and spondylitis [49] . Reported rates among patients receiving salvage TORS surgery vary [9,[11][12][13][14][15][16] .…”
Section: Complicationsmentioning
confidence: 99%